Judicial Authority and the Role of the Religious Courts in the Settlement of Sharia Economic Disputes - Suadi, Amran (APPTHI, 2020)
Regulations on the procedures for resolving sharia economic disputes are undeniable. The rapid development of sharia economics requires adequate and holistic regulations. The importance of regulations regarding procedures for resolving sharia economic disputes can also be understood from the notion of sharia economics or what is also known as Islamic economics. Islamic law regulates all human life as a whole. In principle, the settlement of sharia economic disputes is known by two methods. First, litigation settlement is the resolution of legal disputes or conflicts through the courts. Second, non-litigation settlement, which is the settlement of legal problems outside the judicial process. In providing justice for litigants, Religious Court judges are not only required to understand the sharia aspect but also have to understand the politics of economic law because sharia economics is part of national legal politics in general. Sharia economic law deals with two important aspects. The first is business, and the second is sharia law. The judges of the Religious Courts need to understand the political economy in the business world. All contracts will be tested with the conventional fiqh muamalah concept, even though some contracts practiced in Islamic banking currently have several products that are modifications of conventional fiqh concepts mixed with business concepts in the modern world through the epistemological approach of al-maslahah al-mursalah. In order to carry out its role in sharia economic dispute resolution, in line with community demands, the Religious Courts of the Supreme Court of the Republic of Indonesia has increased the human resource preparation program in the sharia economic law. Various efforts continue to be made, from technical guidance activities for religious court judges, certified sharia economic education and training to legal discussions with the theme of sharia economic law. Abstrak Pengaturan mengenai tata cara penyelesaian sengketa ekonomi syariah tidak dapat dipungkiri, perkembangan ekonomi syariah yang pesat dan pesat memerlukan pengaturan yang memadai dan holistik. Pentingnya pengaturan mengenai tata cara penyelesaian sengketa ekonomi syariah juga dapat dipahami dari pengertian ekonomi syariah atau yang juga dikenal dengan ekonomi syariah. Hukum Islam mengatur seluruh kehidupan manusia secara keseluruhan. Pada prinsipnya penyelesaian sengketa ekonomi syariah dikenal dengan dua cara. Pertama, penyelesaian litigasi, yaitu penyelesaian sengketa atau konflik hukum melalui pengadilan. Kedua, penyelesaian non-litigasi, yaitu penyelesaian masalah hukum di luar proses peradilan. Dalam memberikan keadilan bagi para penggugat, hakim Pengadilan Agama tidak hanya dituntut untuk memahami aspek syariah, tetapi juga harus memahami politik hukum ekonomi karena ekonomi syariah merupakan bagian dari politik hukum nasional pada umumnya. Hukum ekonomi syariah berkaitan dengan dua aspek penting. Pertama, aspek bisnis, kedua adalah aspek hukum syariah. Hakim Pengadilan Agama perlu memahami ekonomi politik dalam dunia bisnis. Semua akad akan diuji dengan konsep fiqh muamalah konvensional, meskipun beberapa akad yang dipraktikkan di perbankan syariah saat ini memiliki beberapa produk yang merupakan beberapa modifikasi konsep fiqh konvensional yang dipadukan dengan konsep bisnis di dunia modern melalui pendekatan epistemologi al-maslahah almursalah. Dalam rangka menjalankan perannya di bidang penyelesaian sengketa ekonomi syariah, sejalan dengan tuntutan masyarakat, Peradilan Agama Mahkamah Agung Republik Indonesia telah meningkatkan program penyiapan sumber daya manusia di bidang hukum ekonomi syariah. Berbagai upaya terus dilakukan, baik melalui kegiatan bimbingan teknis bagi hakim pengadilan agama, pendidikan dan pelatihan ekonomi syariah bersertifikat, hingga diskusi hukum dengan tema hukum ekonomi syariah. Kata kunci: Pengadilan Agama, Ekonomi Syariah, Sengketa Hukum, Otoritas Pengadilan